Predicting Outcome in Acute Organophosphorus Poisoning With International Program On Chemical Safety Poison Severity Score (Ipcs Pss) Grading in Dhaka Medical College Hospital - Kabir, Sheikh Khairul; Alam, Abu Sadat Md Moinul; Alam, Mohammed Syedul; Islam, Mohammad Shaiful; Chowdhury, Muhammad Moazzem Hossain; Paul, Sujat (Journal of Chittagong Medical College Teachers' Association, 2015)
Organophosphorus pesticide poisoning kills around two million people each year, principally due to self poisoning in the Asia-Pacific region. This is a cross-sectional study which was conducted to assess whether patients at high risk of death in acute organophosphorus poisoning could be identified accurately using International Program on Chemical Safety Poison Severity Score (IPCS PSS) and recording clinical parameters soon after admission in Department of Medicine Dhaka Medical College Hospital (DMCH) for a period of six months after approval of the protocol. The study was carried out from March 2013 to August 2013 in the Department of Medicine, DMCH. Eighty patients with detailed information's were obtained according to predesigned protocol. Complete history was taken either from patient or accompanying attendants. Thorough clinical examination was done. Relevant investigations report was collected. All the information's were recorded and collected data were classified, edited, coded and entered into the computer for statistical analysis by using Statistical Package for Social Sciences (SPSS) version - 17. Among the 80 cases, IPCS PSS grade I presentation was more frequent which was 71.2%, followed by grade III 15.0% and grade II presentation (IPCS PSS) 13.8%. The IPCS PSS cut grade H or III was a predictor of outcome as the IPCS PSS itself and Area Under Curve (AUC) of 0.936 with sensitivity of 1.0 and specificity 0.872. In grade I, 71.3% were cured and there was no death, in grade II, 13.8% were cured and there was no death. In Grade III, 12.5% were cured and 2.5% were found death. The present study indicated that the International Program on Chemical Safety Poison Severity Score (IPCS PSS) grading was good predictor of outcome in acute organophosphorus poisoning. Patients who presents with IPCS PSS grade II and III need to be treated accordingly and monitored closely. JCMCTA 2015 ; 26 (1) : 25-29